PENERAPAN MEDIA PEMBELAJARAN SEGITIGA JOKOWI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 09 LUNANG - Aulia, Aisyah Nurul; Dwiana, Ari Aprilia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Mathematics lessons in elementary school are synonymous with difficult lessons, especially in distance, speed and time materials. This is evidenced by the results of a pre-research questionnaire which showed that 60% of students did not like mathematics lessons. Therefore, a visual learning medium that attracts students' interest is needed. This study aims to find out the extent to which the application of Jokowi's triangle media can improve students' mathematics learning outcomes. This research was conducted with a type of classroom action research with qualitative and quantitative approaches (mixed methods). The data collection tools used are observation sheets, tests and documentation, this research was carried out in two cycles. Based on the results in the first cycle, it shows that the average student score is 68.5 with a percentage of 70.83% of students achieving the minimum completeness criteria (KKM), which has shown a slight increase compared to before using the Jokowi triangle media. Then improvements were made to the plan and implementation in the second cycle, it was found that the average student score increased significantly to 84.5 with 87.5% of students achieving the minimum completeness criteria (KKM). Based on the results of the study, the application of Jokowi's triangle learning media is said to be feasible to help improve students' mathematics learning outcomes and get positive responses from teachers and students.